Encouraging Sustainable Accountability in Public Sector Organizations: Digital Transformation in the Procurement Bureau of Goods/Services of the Regional Secretariat of East Java Province - Ardi Kasmono; Maulida Mahfuzhatul Ashudi; Rudi Purwono; Nuri Herachwati (Dinasti Publisher, 2024)
This study aims to analyze the digital transformation in procurement of goods/services at the Procurement Bureau of Goods/Services of East Java Province and how this process contributes to increased accountability. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews with informants selected from purposive sampling. Data were analyzed with the stages of data reduction, presentation, drawing conclusions and verification. Data validity checks with triangulation. Digital transformation at the Procurement Bureau of Goods/Services plays an important role in increasing transparency and accountability. However, obstacles such as internal resistance and limited human resources need to be overcome to optimize its effectiveness. There are several aspects that can be redeveloped to maximize the existing digital climate, including developing a comprehensive platform that facilitates the entire procurement process electronically. This study provides theoretical contributions to the study of information technology adaptation at the organizational level, especially in the context of digital transformation. Most digital transformation studies use a maturity model, but this article chooses an alternative approach by using a contemporary framework that allows for in-depth analysis of various aspects of transformation. This study also offers practical contributions to governance by providing a more holistic, critical and substantial perspective.